Flow in Microchannels between Sealing Surfaces of Casing Connections: LBM Simulation - Feng Ye; Feng Chen; Wenchang Wang; Renliang Zhang; Xing Zhou; Ken Qin; Qinfeng Di (Geofluids, 2023)
Great difficulties have been encountered in the study of the seal failure of casing connection. The in situ microscopic seal surfaces under complex loads are hard to be obtained due to the engagement characteristics of thread. In this study, a method to construct the microscopic seal surfaces of a specified 7″ casing PTC under complex loads was proposed. Then, the lattice Boltzmann method (LBM) was applied to simulate the fluid flow inside the microchannel between the seal surfaces. The effect of pressure gradient and wettability on the flow behavior of a multicomponent fluid system at the microscopic scale was analyzed. Pressure gradient has a huge influence on the volume fraction of sealing compound and the average velocity of displacing fluid. The volume fraction of sealing compound decreases with the increase of pressure gradient. Break-through can be observed for fluid systems with relatively larger pressure gradient. For the systems with Δp=0.658, Δp=0.439, and Δp=0.219, the break-through time steps are around 61000, 99000, and 295000, respectively. Wettability has huge impact on the distribution of sealing compound, and break-through was not observed for the fixed pressure difference Δp=0.110 with various wettability. It is expected to provide some new insights for understanding the seal failure of casing connections at the microscopic level.